2018
DOI: 10.1007/s00392-018-1354-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of hypertrophic cardiomyopathy in children

Abstract: A definite genetic diagnosis can be reached in nearly 80% with HCM of childhood onset. Next-generation sequencing in conjunction with a multidisciplinary cooperation can enhance the diagnostic yield substantially. This may be important for risk stratification, treatment planning and genetic counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
16
0
5
Order By: Relevance
“…The observation that the development of left ventricular hypertrophy in individuals with familial disease often occurs during the period of somatic growth in adolescence has led to the suggestion that sarcomeric protein disease in very young children is rare 61,62 . However, studies of children with HCM have shown that, as in adults, sarcomeric protein gene mutations account for approximately 50% of cases of idiopathic HCM, even in infants and young children 63,64 .…”
Section: Childhood-onset Hcmmentioning
confidence: 99%
“…The observation that the development of left ventricular hypertrophy in individuals with familial disease often occurs during the period of somatic growth in adolescence has led to the suggestion that sarcomeric protein disease in very young children is rare 61,62 . However, studies of children with HCM have shown that, as in adults, sarcomeric protein gene mutations account for approximately 50% of cases of idiopathic HCM, even in infants and young children 63,64 .…”
Section: Childhood-onset Hcmmentioning
confidence: 99%
“…In this review we have chosen to discuss them due to the increased cardiac and therapeutic options related to these disorders. Cardiac manifestations include: cardiomyopathies (CMPs) mainly in their dilated and hypertrophic forms [ 1 , 5 , 6 , 7 , 8 ]; heart rhythm changes, including atrioventricular conduction defects (AVCD); supraventricular tachycardia (SVT); atrial fibrillation (AF) and life threatening ventricular arrhythmias (VA). (However, other less frequently observed manifestations in children include structural cardiac defects such as valvular abnormalities) [ 1 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cirino et al compared the results from NGS panels in 41 HCM patients with whole genome sequencing (WGS) and concluded that WGS and panel testing provided similar diagnostics yield in adult patients [37]. In contrast, Rupp et al studying young patients with diagnosis of HCM before 18 years concluded that WES/WGS was an alternative after negative panel diagnostics [38]. Rupp et al pointed out that panels analyzing genes associated with CM should also focus on multisystemic conditions when applied in younger children.…”
Section: Discussionmentioning
confidence: 99%